Análisis de la eficiencia de los sistemas logísticos en la empresa alinse y anexos para la creación de un manual de procedimientos - Pivaque Quimis, Katherine Jenniffer (2015)
Many companies maintain a logistics process, which allows perform their functions so as to generate customer satisfaction, but when there are problems within these processes that handle the logistics can mean a decrease in sales and even loss customer. So this paper analyzes the efficiency of logistics systems in the company and Annexes Alinse the purpose is the creation of a manual of procedures to optimize the resources that are related to the logistics company…..